Quantitative Analysis of Data from Participatory Methods in Plant Breeding - Bellon, M.; Reeves, J. (International Maize and Wheat Improvement Center, 2002)
Although participatory plant breeding is gaining greater acceptance worldwide, the techniques needed to assess it are not well known. The papers in this volume address the three themes of the workshop: designing and analyzing joint experiments involving variety evaluation by farmers; identifying and analyzing farmers' evaluations of crop characteristics and varieties; and dealing with social heterogeneity and other research issues.